Tratamento das úlceras no pé diabético com gesso de contato total: revisão da literatura - Santos, Alexandre Leme Godoy dos; Fernandes, Túlio Diniz; Tolentino, Ana Carla; Parisi, Maria Candida; Ortiz, Rafael Trevisan; Lima, Ana Lúcia Lei Munhoz (Tobillo y Pie, 2015)
Diabetes prevalence is 8.1% in the South and Central American population. Diabetic foot ulcers (DFU) and Charcot neuroarthropathy (CN) are important complications resulting from neuropathy of the diabetic foot. One of the biggest effects of the global diabetes epidemic, besides the devastating health consequences for people with diabetes, is its economic impact. Diabetes complications are causing economic havoc to those living with the disease, their families and ultimately whole countries, threatening economic development. On this scenario, foot off-loading is considered an essential part of adequate treatment associated with the management of glycemia control, peripheral arterial disease control, infection control and with tissues debridement. Therefore, it becomes important perform a review of literature evidence-based about using off-loading for treatment of DFU. The purpose of this article is to highlight the evidence-based literature on offloading the DFU with Total Contact Casting (TCC) demonstrating why it should be integrated into the standard of care of DFUs in Brazil and Latin America.